DEAD ONLINE: PRACTICES OF POST-MORTEM DIGITAL INTERACTION - Kiel, Paula (AoIR Selected Papers of Internet Research, 2015)
Since their nascence communication technologies have been associated with death, triggering fantasies of dismantling boundaries between death and everyday life. This paper, examines recently emerging digital platforms designed to enable post-mortem interactions as a site in which social meanings of death and the dead are formed, negotiated and modified. Using a multimodal analysis of websites dedicated to post- mortem interaction, this paper aims to answer the questions: How are practices of post- mortem digital interaction constructed through websites designed to enable post- mortem digital interaction? And what do these constructions contribute to the contemporary social construction of death?